2013
DOI: 10.1111/trf.12336
|View full text |Cite
|
Sign up to set email alerts
|

Management of infants born with severe neonatal alloimmune thrombocytopenia: the role of platelet transfusions and intravenous immunoglobulin

Abstract: Transfusion of random-donor PLTs alone was effective at correcting critically low PLT counts and should be considered as first-line treatment of newborns with unexpected severe NAIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 16 publications
1
23
1
4
Order By: Relevance
“…Smaller observational studies have reported on the effect of random‐donor PTx in FNAIT. Kiefel et al () reported a rise in platelet count of >80 × 10 9 /l after treatment with one or two transfusions in 10 newborns and Bakchoul et al () demonstrated a platelet count above 30 × 10 9 /l for longer than 24 h after one random‐donor PTx in five out of seven cases compared to two out of four cases treated with HPA‐compatible platelets. In our cohort, 46 newborns were treated solely with (one or more) PTxs.…”
Section: Distribution and Effect Of Postnatal Treatmentmentioning
confidence: 99%
“…Smaller observational studies have reported on the effect of random‐donor PTx in FNAIT. Kiefel et al () reported a rise in platelet count of >80 × 10 9 /l after treatment with one or two transfusions in 10 newborns and Bakchoul et al () demonstrated a platelet count above 30 × 10 9 /l for longer than 24 h after one random‐donor PTx in five out of seven cases compared to two out of four cases treated with HPA‐compatible platelets. In our cohort, 46 newborns were treated solely with (one or more) PTxs.…”
Section: Distribution and Effect Of Postnatal Treatmentmentioning
confidence: 99%
“…Secondly, improvements in the management of pregnant women with a positive history of FNAIT have resulted from systematic studies of the use of antenatal immunomodulation with IVIG in place of invasive treatment (in utero platelet transfusion). 224,225 Finally, large screening studies have shown the potential benefit of testing in combination with planned delivery and prophylactic perinatal platelet transfusion.…”
Section: European Research Contributionsmentioning
confidence: 99%
“…Neonatal alloimmune thrombocytopenia (NAIT) is the most common cause of severe thrombocytopenia in newborns . Typical patients with NAIT develop petechiae within minutes of birth, followed by ecchymosis and cephalohematoma . After delivery, the greatest risk of hemorrhage is in the first 96 hours of life.…”
Section: Discussionmentioning
confidence: 99%
“…After delivery, the greatest risk of hemorrhage is in the first 96 hours of life. Thrombocytopenia in patients with NAIT resolves naturally within 1‐2 weeks after birth . Because there were also no hemorrhagic episodes in his perinatal period, we judged that there was no association between thrombocytopenia and NAIT in this case, although anti‐human platelet antigen alloantibodies were not tested.…”
Section: Discussionmentioning
confidence: 99%